Glioblastoma multiforme intraxial metastasis to the conus medullaris with primary disease under control: a rare unexpected finding. (June 2013) - Sabatino, G.; Della Pepa, G. M.; Esposito, G.; Brodbelt, A.
Abstract We report on glioblastoma multiple spinal intraaxial metastases with primary disease radiologically under control. The case highlights glioblastoma biological behavior and spread mechanisms; dissemination may have occurred initially and been controlled by chemotherapy, or more likely, is an indicator that even if radiologically dormant, disease is unlikely biologically inactive.